Effect of microwave treatment on tensile properties of sugar palm fibre reinforced thermoplastic polyurethane composites - Mohammed, A. A.; Bachtiar, Dandi; M. R. M., Rejab; Siregar, J. P. (Elsevier, 2018)
The effect of microwave treatment on the tensile properties of treated sugar palm fibre with 6% NaOH reinforced thermoplastic polyurethane composites was investigated. Firstly, the sugar palm fibres were treated by 6% alkali solution. Then, microwave treatment was used to treat the alkali treated sugar palm fibres. Three types of temperatures (i.e. 70, 80 and 90 °C) were applied in microwave treatment. The extruder and hot press machines were used to mixing the sugar palm fibres and polyurethane resin, and fabricate the composites. Tensile properties (i.e. tensile strength, tensile modulus and elongation at break) were studied by following the ASTM D-638 standard. The highest tensile strength was recorded 18.42 MPa with microwave temperature at 70 °C and 6% alkali pre-treatment. Therefore, the temperature 70 °C of microwave treatment may consider the best degree cent grate.